Surfactant enhanced-spectrophotometric determination of uranium (VI) at trace levels by using eriochrome black T as a chelating agent - Gürkan, Ramazan; Ulusoy, Halil İbrahim; Akçay, Mehmet (Eclética Química, 2014)
A sensitive and relatively selective spectrophotometric method is proposed for the rapid determination of uranium using Eriochrome Black T (EBT) being a 2,2’-dihydroxy azo benzene derivative metal indicator in the presence of cationic surfactant of N-cetyl N,N,N-trimethylammonium bromide (CTAB). The complex formation reaction between EBT and uranyl ion, UO22+ is instantaneous in presence of NH3/NH4Cl buffer at pH 9.5 and the absorbance as analytical signal remains stable for over 6 h. CTAB as cationic surfactant and polyethylene glycol p-(1,1,3,3-tetramethylbutyl)-phenyl ether, octyl phenol ethoxylate (Triton X-100) as nonionic surfactant are used for improving the sensitivity and solubility of the analytical system, respectively. The proposed method allows the determination of uranium in the concentration range of 0.025-2 μg mL–1 with a molar absorption coefficient of 92440.60 L mol–1 cm–1 and Sandell’s sensitivity of 2.92 μg cm2- in micellar medium while it allows the determination of uranium in the concentration range of 0.25-2.5 μg mL–1 with a molar absorption coefficient of 57019.44 L mol–1 cm–1 and Sandell’s sensitivity of 4.74 μg cm2- at 565 nm in water. The detection limit is 4.60 μg L–1 (CDL: 3Sb/m) at 637 nm with a bathochromic shift of 72 nm.